The Emerging Role of MXenes in Cancer Treatment - Salkho, Najla (2025)
MXenes are relatively new 2D materials made up of carbides and/or nitrides of transition metals with a chemical formula Mn+1XnTx. They are usually fabricated by chemically etching a ceramic phase. MXenes possess tunable catalytic, optical, and electronic properties, which have attracted significant research interest, primarily in energy storage and biosensing applications. Since their first fabrication in 2011, there has been a rapid increase in studies investigating the use of MXenes in a wide range of applications. In this review, the synthesis methods of MXenes are discussed. Then, the potential application of MXenes in cancer treatment is highlighted based on current research. The ability of MXene to convert light, usually NIR (I and II), to heat with improved conversion efficiencies makes it a competitive candidate for photothermal cancer therapy. Moreover, the surface of MXenes can be modified with drugs or nanoparticles, thereby achieving synergistic photo/chemo/, and sonodynamic therapy. This review also examines the available research on the biocompatibility and cytotoxicity of MXenes.